2018
DOI: 10.1155/2018/4808046
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Genetic Markers and Age Effectively Facilitates the Identification of People with High Risk of Preeclampsia in the Han Chinese Population

Abstract: Objective This study aimed to analyze the possible association between known genetic risks and preeclampsia in a Han Chinese population. Methods A total of 156 patients with preeclampsia and 286 healthy Han Chinese women were enrolled and genotyped for 27 genetic alleles associated with preeclampsia in different populations. The association between the genotypes of the individual alleles and preeclampsia and the possible interaction among the alleles were analyzed. Finally logistic models were trained with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…McGinnis et al performed a GWAS study on PE offspring and identi ed a signi cant susceptibility locus (rs4769613) that was nearby the gene FLT1 encoding FMS like tyrosine kinase 1 [25]. Zhou et al selected multiple genetic risk loci that have been reported to be signi cantly associated with PE in other multiethnic cohorts, performed genotype testing in Chinese PE and healthy pregnancies, and found very few risk alleles or genotypes consistent with previous reports [30,31]. Some risk loci even showed opposite effects, i.e., being protective to the Chinese population for the risk alleles or genotypes reported for other ethnicity, further demonstrating the ethnic speci city of PE genetic susceptibility.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…McGinnis et al performed a GWAS study on PE offspring and identi ed a signi cant susceptibility locus (rs4769613) that was nearby the gene FLT1 encoding FMS like tyrosine kinase 1 [25]. Zhou et al selected multiple genetic risk loci that have been reported to be signi cantly associated with PE in other multiethnic cohorts, performed genotype testing in Chinese PE and healthy pregnancies, and found very few risk alleles or genotypes consistent with previous reports [30,31]. Some risk loci even showed opposite effects, i.e., being protective to the Chinese population for the risk alleles or genotypes reported for other ethnicity, further demonstrating the ethnic speci city of PE genetic susceptibility.…”
Section: Introductionmentioning
confidence: 60%
“…5A). The model performs as well as those developed previously that are based on both the genotypes of 5 or 8 PE risk loci and clinical factors [31]. We also included the 8 previously identi ed loci and the age and BMI at pregnancy, and trained different regression or machine learning models.…”
Section: A Multi-gene Model Predicts Chinese Women With High Preeclam...mentioning
confidence: 88%
See 2 more Smart Citations
“…2 Genetic and environmental factors have been known to have contributions for preeclampsia phenotype. [3][4][5] Abnormality of trophoblast invasion to myometrium is followed by endothelial disfunction local in placenta, then spreads to maternal circulation. This abnormality involved unbalanced proangiogenic and antiangiogenic factors.…”
Section: Introductionmentioning
confidence: 99%